Objectively measured sleep and β-amyloid burden in older adults: A pilot study. (12th August 2014) - Spira, Adam P; Yager, Christopher; Brandt, Jason; Smith, Gwenn S; Zhou, Yun; Mathur, Anil; Kumar, Anil; Brašić, James R; Wong, Dean F; Wu, Mark N
Background/aims: Although disturbed sleep is associated with cognitive deficits, the association between sleep disturbance and Alzheimer's disease pathology is unclear. In this pilot study, we examined the extent to which sleep duration, sleep quality, and sleep-disordered breathing are associated with β-amyloid (Aβ) deposition in the brains of living humans. Methods: We studied 13 older adults (8 with normal cognition and 5 with mild cognitive impairment). Participants completed neuropsychological testing, polysomnography, and Aβ imaging with [ 11 C]-Pittsburgh compound B. Results: Among participants with mild cognitive impairment, higher apnea–hypopnea index and oxygen desaturation index were associated with greater Aβ deposition, globally and regionally in the precuneus. There were no significant associations between sleep-disordered breathing and Aβ deposition among cognitively normal participants. There were no significant associations between sleep duration or sleep fragmentation and Aβ deposition. Conclusion: These preliminary results suggest that among older adults with mild cognitive impairment, greater sleep-disordered breathing severity is associated with greater Aβ deposition.